Pengaruh Konservatisme Akuntansi Terhadap Penilaian Ekuitas Perusahaan dengan Kepemilikan Manajerial dan Dewan Direksi sebagai Variabel Moderasi (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021) - Raymond Meivan Revido Ginting; Fitria Husnatarina; Golda Belladonna Umbing; Tatik Zulaika; Rahmiati Rahmiati; Agus Satrya Wibowo (Universitas 45 Surabaya, 2023)
This study aims to determine the effect of accounting conservatism, managerial ownership in moderating the relationship between accounting conservatism on valuation of equity and the board of directors in moderating the relationship between conservatism and valuation of equity in Manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. In this study, the population used was manufacturing companies listed on the IDX for the 2019-2021 period. Based on this research, out of 288 observations, only 239 data will be analyzed because the outlier test results and data transformation are in the form of Natural Logarithms. The data obtained were then analyzed using the SPSS version 25 application tool. The results of this study indicate that accounting conservatism has a negative but not significant effect on equity valuation. Then, in moderation the results show that managerial ownership has a positive but not significant effect in moderating the relationship between accounting conservatism on equity valuations and the board of directors has a positive but not significant effect in moderating the relationship between accounting conservatism on equity valuations. Suggestions through the results of this study are that in creating reliable financial reporting the company should adjust to the standards that have been set. Then, investors and creditors, must consider in working with a company or in making investment decisions, especially if the company does not have quality financial reporting and for further researchers who wish to conduct similar research, it is better to add five years of research or more. or researching on other types of industries to find out the variations in the results of the research variables contained in this study.